Rehabilitation For Addicts For Victims To Spike Narcotics In The Penal System - Priambodo Adi Wibowo (Faculty of Law, Merdeka University Surabaya, 2017)
Ratio decidendi in the decision for the rehabilitation of drug addicts is the judge considering the health condition of drug addicts in the decision making. The health condition of drug addicts known by requesting information from the doctors associated with the disease and how to handle. In addition to the health of drug addicts, the ratio decidendi in the decision on rehabilitation is to meet the criteria that addicts are victims, the abuse of drugs for themselves, not dealers, and personal possession of drugs. Ius constituendum as criminal law aspired are calls for legal protection to drug addicts. Legal protection is realized by way of clarifying the characteristics of drug addicts as victims that distinguishes between addicts with dealers, as well as clarify the ownership category. Legal protection is also realized by providing a sufficient rehabilitation in human resources, facilities and systems. Recommendations from the results of this study are setting penalties for abusers of drugs should be revised and lead to aspects of treatment for drug addicts, which is realized with the rehabilitation of drug addicts as an attempt depenalitation. This is consistent with the concept of self-victimizing victims. BNN, Ministry of Health, IPWL and communities should participate actively in the implementation of rehabilitation by building institutions of rehabilitation.